Peran Intelijen dalam Keberlangsungan Demokrasi dan Hak Asasi Manusia di Indonesia - Muhammad Arbani (Syntax Corporation Indonesia, 2023)
This paper discusses the dynamics of the role of intelligence in the reform era in relation to democracy and human rights. Intelligence reform places intelligence more ideally attuned to reform values. However, intelligence practices in the reform era were not as perfect as imagined. In this paper, there are intelligence opportunities and challenges in the future, as part of intelligence development efforts. This paper uses the theory of democratic intelligence owned by Uri Bar-Joseph. The conclusion of this paper is that intelligence as a tool of state security institutions can also have a great opportunity to promote democratic values if law enforcement is really implemented. However, these efforts are not as easy as turning the palm of the hand, because intelligence is still facing challenges that have not been resolved to date.